L’économie de fonctionnalité entre éco-conception et territoire : une typologie - Nicolas Buclet (Développement Durable et Territoires)
The aim of this paper is to indicate new research tracks to be explored in the field of economy of functionality. The observation of the implementation of economy of functionality shows that it is not possible to consider it as a sustainable development strategy per se. Questions are entire concerning its potential, in order to incent companies to adopt a more systematic approach in eco-design, as well as in taking into account sustainable aspects at a local level. In order to progress, the paper proposes a new typology of the economy of functionality, from which it is possible to reflect to this economic model through both eco-design and local questions of development.